Effect of 3 versus 3 small sided handball game training on aerobic capacity and anaerobic endurance of male handball players - Chittibabu, B.; Weber, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Today handball is more dynamic and faster than ever before. During handball game players perform several high intensity repeated sprint bouts of short duration with partial rest (Póvoas et al. 2012; Sibila, Vuleta & Pori 2004) which is associated with good endurance capability and anaerobic endurance of players. Developing fitness through skill based conditioning is more suitable than traditional training. Small sided games are a type of skill based conditioning which combines both sports specific skills and fitness. Therefore, the aim of our study is to assess the effect of 3 versus 3 small sided handball game training on aerobic capacity and anaerobic endurance of male handball players. Methods: Twenty four (24) male handball players were selected and randomly classifieds into two groups namely 3 versus 3 small sided handball training group (3 vs 3 = 12) and control group (CON = 12). Twenty four handball players were tested on aerobic capacity and anaerobic endurance before the start, at middle and after twelve weeks of training. The 3 versus 3 small sided handball training was performed three days per week for twelve weeks. To assess the training effect 2 × 3 repeated measure ANOVA on last factor repeated was performed. Results: The result of our study showed that six and twelve weeks of 3 versus 3 small sided handball game training significantly improved aerobic capacity (F=51.36, p=0.000) and anaerobic endurance (F=32.48, p = 0.000) of handball players. Discussion: The result of our study showed that 3 versus 3 small-sided handball game has large effect and which confirm that 8.66% improvement in aerobic capacity and anaerobic endurance by 6.74% improved after twelve weeks of training. Coutts and his colleagues (2010) clearly state that game based training improves both fitness (Chittibabu 2013) and skill. The improvement in VO2 max is associated with changes in cardiovascular function and anaerobic endurance is enhanced through faster lactate removal and PCr restoration, thus enhancing power and force recovery (Bassett et al. 1991). It is concluded that 3 versus 3 effective in improving aerobic capacity and anaerobic endurance of male handball players.